Meningkatkan Metode Pembelajaran Make a Match Dalam Meningkatkan Kemampuan Membaca Permulaan Pada Anak Disleksia - khairunnisa, oka (RC-INSTITUT, 2019)
This study discusses the problems found in SD N 44 Sungai Lareh Padang, namely a 10-year-old dyslexic student who has difficulty reading early. This study aims to reveal whether the effective method of learning to make a match can improve reading skills in dyslexic children. The research method in this study is a Single Subject Research (SSR) with A-B-A design. Measure and collect data in the first baseline (A1) condition continuously for 5 observations. Providing interventions using the make a match (B) method was carried out for 8 observations. Give a second baseline condition (A2) for 4 observations. This research data collection technique is to provide tests and study documentation. Based on the results of data analysis under conditions that showed an increase in the ability to read the beginning positive. Overlap of data in the analysis between conditions, at baseline (A1) and intervention (B) is 40% and overlap of data at baseline (A2) and intervention is 12.5%. Based on the results of the analysis of these data shows that the make a match learning method can improve the ability to begin reading in dyslexic children.